Advancements in the development of TiO 2 photoanodes and its fabrication methods for dye sensitized solar cell (DSSC) applications. A review - Ahmad, M.S.; Pandey, Adarsh Kumar; Rahim, Nasrudin Abd (Elsevier, 2017)
Dye sensitized solar cells (DSSCs) are widely studied for the safe and reliable energy supply. Due to its low fabrication cost, eco-friendly production and competitive efficiency, this is the promising technology. The components of DSSC which combine to form a photo conversion device are the conducting substrate, dye, photoanode, catalyst and electrolyte. Each component has its own importance but among them photoanode is probability the main component which determines the energy conversion efficiency. Various photoanode materials have been trialled to date. Among them Zn and TiO2 are widely recognized, researched and investigated. In this review attempt will be made to examine the strategies to improve the efficiency of TiO2 photoanode. This review is dedicated to the TiO2 photoanode, its properties, issues related to TiO2 photoanode, various improvement approaches, fabrication methods successfully trialled so far followed by market potential of the DSSC technology, conclusion and recommendations.